Effect of 100% Chamomile Extract on The Number of Staphylococcus Aureus Bacterial Colonies in Orthodontic Bracket (In Vitro Study) - Prasetyadi, Tjokro; Deviyanti, Sinta; Maharani, Karlina Rahma (YARSI Dental Journal, 2024)
Abstract Background: Fixed orthodontic appliances in malocclusion treatment consist of several components. Bracket components in fixed orthodontic appliances cause side effects such as gingivitis due to retention of Staphylococcus aureus bacterial plaque. Chamomile flower extract contains antibacterial compounds, α-bisabolol. Objective: To analyze 100% chamomile extract effectiveness of Staphylococcus aureus bacteria colonies in orthodontic bracket. Methods: This study using post test only control group design. Chamomile extract procure from percolation methods. Eighteen orthodontic brackets were divided into three groups, soaked in artificial saliva for 1 hour, contaminated with Staphylococcus aereus, then immersed in 100% chamomile flower extract solution, 0,2% chlorhexidine (positive control), and aquadest (negative control) for 30 minutes. Total of 0,1 ml of multilevel serial dilution from three different groups was dripped and streaked onto Brain heart infusion agar, incubated for 24 hours at 37oC for further colony counting tests. Results: S. aureus bacteria colonies in orthodontic bracket group with 100% chamomile flower extract solution was not significantly different from 0,2% chlorhexidine group (p>0,05), but significantly lower than aquadest group (p<0,05). Conclusion: The 100% chamomile extract solution as effective as Chlorhexidine 0,2% in reducing number of Staphylococcus aureus colonies in orthodontic braket. Keywords: Staphylococcus aureus, the 100% chamomile extract, Chlorhexidine 0,2%, orthodontic brackets.